A New Method for Designing Inextensible Flows of Spacelike Curves in 4-Dimensional LP-Sasakian Manifolds - Korpinar, Talat; Turhan, Essin (Springer India, 2015)
In this paper, we construct a new method for inextensible flows of spacelike curves in a conformally flat, quasi conformally flat and conformally symmetric 4-dimensional LP-Sasakian manifold. Using the Frenet frame of the given curve, we present partial differential equations. We give some characterizations for curvatures of a spacelike curve in a conformally flat, quasi conformally flat and conformally symmetric 4-dimensional LP-Sasakian manifold.
Keywords: Flow; Fluid flow; LP-Sasakian manifold; Partial differential equation